Irisin as a predictor of bone metabolism in Han Chinese Young Men with pre-diabetic individuals - Junru Liu; Xing Wang; Dongmei Fan; Lina Sun; Weinan Zhang; Fuzai Yin; Bowei Liu (BMC Endocrine Disorders, 2022)
Abstract Background Irisin is a novel myokine both in mice and humans, and it can also be secreted by adipose tissue and the liver in a small amounts. There are few studies on irisin and bone metabolism. The aim of this study was to assess the relationship between serum irisin levels and bone metabolism and analyze its related factors in Han young male with pre-diabetic individuals. Methods This cross-sectional study included 41 pre-diabetes and 45 normal glucose tolerance (NGT). Anthropometric measurements, including height, weight, waist circumference (WC), and bone mineral content (BMC), were performed. All patients underwent an oral glucose tolerance test (OGTT) after 8 h of fasting, and the levels of glucose, insulin, lipids, serum irisin and bone turnover markers were measured. Results The levels of serum irisin (4.4 ± 1.4 vs. 6.3 ± 1.5 µg/mL), P1NP and OC were significantly lower and CTX was significantly higher in the pre-diabetes group (P < 0.05). BMC did not differ in the two groups (P > 0.05). Serum irisin levels negatively correlated with BMI (r =-0.325), FPG (r =-0.329), TG (r =-0.339) (P < 0.05) in NGT individuals. Serum irisin levels positively correlated with P1NP (r = 0.398), OC (r = 0.351), HDL-C (r = 0.432) and negatively correlated with FPG (r = -0.725), 2 h-PG (r = -0.360) (P < 0.05) in pre-diabetic individuals. Multiple regression analysis revealed that Serum irisin (β = 9.768, P = 0.025) and WC (β = -2.355, P = 0.002) were significant independent predictors for P1NP. Conclusion Bone turnover markers were changed rather than bone mineral content in young men with pre-diabetes. In pre-diabetes individuals, serum irisin levels were reduced and close relationship with P1NP. Falling irisin levels may be a predictor of decreased bone formation in Han young men with pre-diabetes individuals.